Point-of-care ultrasonography for risk stratification of non-critical suspected COVID-19 patients on admission (POCUSCO): A prospective binational study. - François Morin; Delphine Douillet; Jean François Hamel; Dominique Savary; Christophe Aubé; Karim Tazarourte; Kamélia Marouf; Florence Dupriez; Phillipe Le Conte; Thomas Flament; Thomas Delomas; Mehdi Taalba; et al. (PLoS ONE, 2023)
Background Lung point-of-care ultrasonography (L-POCUS) is highly effective in detecting pulmonary peripheral patterns and may allow early identification of patients who are likely to develop an acute respiratory distress syndrome (ARDS). We hypothesized that L-POCUS performed within the first 48 hours of non-critical patients with suspected COVID-19 would identify those with a high-risk of worsening. Methods POCUSCO was a prospective, multicenter study. Non-critical adult patients who presented to the emergency department (ED) for suspected or confirmed COVID-19 were included and had L-POCUS performed within 48 hours following ED presentation. The lung damage severity was assessed using a previously developed score reflecting both the extension and the intensity of lung damage. The primary outcome was the rate of patients requiring intubation or who died within 14 days following inclusion. Results Among 296 patients, 8 (2.7%) met the primary outcome. The area under the curve (AUC) of L-POCUS was 0.80 [95%CI:0.60-0.94]. The score values which achieved a sensibility >95% in defining low-risk patients and a specificity >95% in defining high-risk patients were <1 and ≥16, respectively. The rate of patients with an unfavorable outcome was 0/95 (0%[95%CI:0-3.9]) for low-risk patients (score = 0), 4/184 (2.17%[95%CI:0.8-5.5]) for intermediate-risk patients (score 1-15) and 4/17 (23.5%[95%CI:11.4-42.4]) for high-risk patients (score ≥16). In confirmed COVID-19 patients (n = 58), the AUC of L-POCUS was 0.97 [95%CI:0.92-1.00]. Conclusion L-POCUS performed within the first 48 hours following ED presentation allows risk-stratification of patients with non-severe COVID-19.